PERNIKAHAN DINI PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF (STUDY KASUS PENGADILAN AGAMA KABUPATEN MALANG) - Muhammd Zulqifli Akbar; Ach Faisol; Ibnu Jazari (Jurnal Hikmatina, 2022)
Early marriage has become a social problem due to promiscuity, way of life and culture in community groups. This problem is still attached to the majority of the people of Malang Regency. The purpose of this research is to clarify the issue of early marriage and positive law, as well as Islamic views  on early marriage. This study uses descriptive qualitative research methods. This research uses descriptive qualitative research method. Data collection is done by interview and documentation techniques. The results of the study indicate that early marriage in Malang Regency is classified as "very sad" with applications for marriage dispensation reaching 5 to 10 cases every day. The positive legal perspective of Indonesia through Law Number 16 of 2019 concerning marriage has determined the minimum age for marriage, namely 19 years for both men and women. Islamic law through the Compilation of Islamic Law (KHI) has determined the minimum age at marriage for the  bride and groom to achieve physical and mental maturity  to achieve the goal of a happy and harmonious marriage.Kata kunci: hukum islam, hukum positif, usia dini, dispensasi nikah, pernikahan